Gender affirming hormone therapy and transgender women fertility: Histologic predictors of germ cell presence - Lina Rigodanzo Marins; Tiago Elias Rosito; Lucia Maria Kliemann; Edson Capp; Helena von Eye Corleta (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2024)
Abstract Objective: Evaluate histological changes in testicular parameters after hormone treatment in transgender women. Methods: Cross-section study with patients who underwent gonadectomy at Hospital de Clínicas de Porto Alegre from 2011 to 2019. Hormone treatment type, route of administration, age at initiation and duration were recorded. Atrophy parameters were observed: testicular volume, tubular diameter, basal membrane length, presence of spermatogonia and spermatids (diploid and haploid spermatozoid precursors). Results: Eighty-six patients were included. Duration of hormone treatment is associated with testicular atrophy and spermatogenesis arrest. Other characteristics of hormone treatment such as age of initiation, route of administration and type of treatment were not associated with testicular histological changes. Testicular volume may predict spermatogenesis arrest. Basal membrane length and tubular diameter ratio is an interesting predictor of germ cell presence. Conclusion: Cross-sex hormone treatment affects testicular germ cell presence. Basal membrane length and tubular diameter ratio reduces inter variability of measurements and better exemplify how atrophic seminiferous tubules are. Fertility preservation should be addressed by healthcare providers in order to recognize gender affirming treatment impact on transgender health.